SCIENCE AS A SUBJECT OF LEARNING IN ISLAMIC UNIVERSITY - Subandi, Muhammad; Mahmoud, Abdelwahab M. (Jurnal Pendidikan Islam, 2016)
This paper aims to searching theological impact when applied a science as a subject of learning at Agrotechnology Department in the Faculty of Sciences and Technology of State Islamic University of Bandung. The atmospheric experiment was implemented as a subject of learning. By observing the atmospheric data recorded, the plant growth measured significantly affected by the implementation of treatments, the best water supply and fertilizer application. Furthermore, it found that local climate has changed, and Schmidt and Ferguson classification of regional rain types is no more valid, thus, should be renewed. The experiment impacted to a science learning program in Islamic University. Climatic change is a natural law affected by human destructed to the nature. It has been affecting farmers to maintain for their plantation activities. When organisms were effort to surviving in warmer and unpredictable condition, that is shows to human kind has to obligatory to the Almighty God.